WATERMELON JUICE USAGE TO DECREASE BLOOD PRESSURE IN ELDERLY WITH HYPERTENSION - Indriana Indriana; Mashuri Mashuri (UNEJ e-Proceeding, 2022)
Hypertension, better known as high blood pressure, is an abnormal increase in blood pressure, both systolic and diastolic. Statistically, watermelon has an effect on reducing blood pressure in hypertensive patients; the blood pressure before administration of watermelon is significantly higher than after administration of watermelon. The CMA Keris Community Service Team implemented community service by providing education in the form of question-and-answer lectures and discussions, as well as examples of watermelon juice products made directly by the team, to 60 elderly people at the Sukoreno Village Hall in Jember Regency. Before carrying out the service, it begins with a letter of application from partners, namely the head of Sukoreno Village, addressed to the D3 Nursing Study Program, Faculty of Medicine, Jember University Nursing, Lumajang Campus. There are three factors that support the success of health education for the public, namely preparation, including cross-sector collaboration, content or theme of counseling, and counseling media. Keywords: hypertension, water melon, health education